EDUKASI PENYIMPANAN DAN PENYAJIAN ASI PERAH SEBAGAI UPAYA MENJAGA KANDUNGAN NUTRISI ASI - Subandrate Subandrate; Ella Amalia; Dwi Indira Setyorini; Safyudin Safyudin (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Exclusive breastfeeding is still not fully carried out by Indonesian mothers. The problem with breastfeeding is the lack of knowledge among mothers and working mothers. To promote exclusive breastfeeding again, educational programs can be carried out. Educational activities are carried out offline at the Prabumulih Mayor's Office Hall. Participants in this community service activity were PKK women from Prabumulih City, with a total of 54 people and ages ranging from 27 years to 71 years. The expert in this activity were dr. Ella Amalia, M.Kes, secretary of the South Sumatra Branch of the Association of Indonesian Breastfeeding Mothers (AIMI), and the national ASI counselor. She informed that breast milk contains sufficient nutrients for the growth and development of infants. Working mothers can continue to provide expressed breast milk (ASIP) to their babies. Giving ASIP to infants requires attention to how it is stored and served. Defrosting ASIP by gradually increasing the temperature, for example, from the freezer to the fridge and then to room temperature, is considered better than direct defrosting with hot water or a heater. Community service activities have been carried out well. This service can provide education to breastfeeding mothers regarding the proper storage and presentation of ASIP.